Networking on the utilization of local natural resources - Herbály-Hekli, Katalin (Applied Studies in Agribusiness and Commerce, 2011)
Together with its partners, Szolnok College is planning to evaluate a new project for networking on the utilization of local natural resources. This project is based on a research work (using the findings of the surveys completed by the representatives of hosts living in the eastern part of Hungary). The project itself is based on the adaptation of the theory of tourism into practice by presenting existing natural values in the supply portfolio of tourist service providers. A unique natural environment can be found alongside a 120 km-long stretch of River Tisza. These natural values interlink and complete each other with respect to Lake Tisza and River Tisza. Regions and settlements situated further from the specified settlements are also rich in natural values which guests will definitely be pleased to get acquainted with. The six landscape centres (including LHH regions) alongside river Tisza (in the two regions) symbolise the interdependent system of the sample area of the project while a single landscape centre in the Pásztó Minor Region embodies a unique character. A register will be prepared for each landscape centre containing unique natural values that can be involved in the tourist supply and handicraft/economic activities (e.g. basket weaving, floodplain economy) that are or can be built on these natural values. A pictorial English/German-Hungarian professional dictionary summarises the distinctive nature of landscape centres. The education material demonstrating the registers is going to be developed both in conventional and electronic form; its spatial IT appearance on the Internet is considered a special feature. The education material will be supplemented with other information currently missing such as those related to environmentally friendly economy, and the legal context. The methodology allows the adaptation of the method in other regions, even in the whole country. The new qualifying and benchmarking system and the trademark managed by a profession-specific cluster that strengthens network co-operation and controls the development guarantee the achievement of high quality tourism.